The Federal Reserve's evolving interpretation and implementation of its mandate - Athanasios Orphanides (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2024)
Throughout its history, the Fed has operated with a muddled mandate that has not explicitly recognized price stability as the primary goal of monetary policy. The Fed's success in maintaining price stability and fostering the good economic performance associated with it has depended on how it interpreted its mandate and implemented its policy strategy. In the 1970s and in the recent past, the Fed interpreted its mandate in an overambitious fashion, placing undue emphasis on the elusive goal of maximum employment. On both occasions, the Fed's strategy proved insufficiently resilient, and high inflation followed. To improve its policy strategy the Fed ought to revert to earlier interpretations of its mandate that acknowledge the primacy of price stability as a policy guide.
Keywords: E32; E52; E58; E61; 330; Federal Reserve; mandate; maximum employment; monetary policy strategy